Studies on Truck Transportation of Timber - Kant, Hari; Sood, K. G. (Indian Forester, 1978)
Since Independence more and more roads are being constructed in foreat areas and trucks have almost monopolised the mode of long distance transportation in the plains as well as in foot hill forests. The present time and cost study has been made to find out the impact of various road standards on the cost of timber transportation by trucks. The observations made in this paper will help in proper planning of road and harvesting programme in similar forest areas.